Success rate of the treatment of early childhood caries under general anesthesia: A retrospective cohort study in different periods - Zhang, Baize; Wang, Junhui; Han, Xinxin; Fang, Ruohao; Wang, Zirui; Hui, Zeming; Chen, Yujiang; Liu, Jiajia; Wang, Xiaojing (Frontiers in Pediatrics, 2023)
The purpose of this study was to evaluate the three-year success rate of the treatment for early childhood caries (ECC) under general anesthesia in different periods (2011 and 2018). Children (<6 years old) who had severe caries and were treated under general anesthesia in 2011 and 2018 were selected and followed up by telephone appointment and clinical examination. Success rate of each treatment was determined and possible factors associated with treatment failure were evaluated. There were 153 patients (with an average age of 48.55±13.37 months) and a total of 2,018 teeth included in the 2011 group. In the 2018 group, there were 273 patients with an average age of 49.01±12.42 months and a total of 3,796 teeth. The success rate in the 2011 group was significantly lower than that in the 2018 group. Teeth with mineral trioxide aggregate (MTA)-capped pulp survived significantly longer than those with calcium hydroxide-capped pulp. The utilization rate of preformed crown restoration was higher than that of resin restoration, and the survival time of dental restorations with preformed crown was prolonged. For posterior teeth, the success rate of indirect pulp capping and pulpotomy was also significantly higher than those without preformed crowns. General anesthesia is a safe and effective behavioral management method for uncooperative children's dental treatment. The use of biocompatible pulp capping materials and preformed crowns improved the success rate of treatment and prolonged the survival time of affected teeth.